Phoenix : a chronological & documentary history, 1865-1976 - Buchanan, James E. (Dobbs Ferry, N.Y. : Oceana Publications, 1978)
A chronology of important events in the history of Phoenix accompanied by pertinent documents.
Includes index.
Bibliography: p.139-143.
Keywords: Phoenix (Ariz.) -- History -- Chronology; Phoenix (Ariz.) -- History -- Sources; Phoenix (Ariz.) -- History